2011
DOI: 10.1002/art.30116
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Wnt pathway activity in mouse serum and kidneys during lupus development

Abstract: Objective. The canonical Wnt/␤-catenin pathway was recently identified as a factor in the pathogenesis of several renal diseases. The aim of this study was to evaluate Wnt signaling activity during disease development in a murine model of lupus nephritis.Methods. Wnt activity and Dkk-1 expression were serially assayed in the serum and kidneys of (NZB ؋ NZW)F 1 mice during progression of lupus nephritis. The effects of serum obtained from mice with lupus and serum-equivalent concentrations of Dkk-1 on mesangial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 38 publications
3
28
0
Order By: Relevance
“…Tveita and Rekvig previously showed that β-catenin-related transcription is elevated in the kidneys of lupus-prone BWF1 mice [24]. We have also observed that renal beta catenin expression and its transcriptional targets is elevated in another mouse model of lupus, B6.Sle1.Sle3 (S3 Fig).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Tveita and Rekvig previously showed that β-catenin-related transcription is elevated in the kidneys of lupus-prone BWF1 mice [24]. We have also observed that renal beta catenin expression and its transcriptional targets is elevated in another mouse model of lupus, B6.Sle1.Sle3 (S3 Fig).…”
Section: Discussionsupporting
confidence: 66%
“…We and others have screened lupus-prone mice and SLE patient serum and find increased β-catenin-related markers [24]. Given the interesting role of this pathway in immunity and tolerance, and the observed changes in several circulating proteins related to this signaling pathway, we examined the potential role of this pathway in lupus.…”
Section: Introductionmentioning
confidence: 99%
“…DKK-1 expression was also increased in these same conditions, and mediated c-Jun, TGF-β1, and fibronectin expression, whereas stable β-catenin expression alleviated DKK-1-induced profibrotic factors, indicating that β-catenin may be a potential therapeutic target of MC dysfunction of diabetic nephropathy (26). In immune-mediated MC injury, the Wnt pathway has been demonstrated to be involved in the anti-Thy-1.1 rat model of glomerulonephritis (27), and development of lupus nephritis (28). However, there is currently scarce in vitro evidence regarding Wnts and β-catenin expression in LPS-stimulated MCs.…”
Section: Discussionmentioning
confidence: 97%
“…For example, using murine models for lupus, it has been shown that Dickkopf-1 (DKK1), a negative regulator of the Wnt/β-catenin pathway, is highly upregulated in the serum during lupus progression (55). Similarly, serum samples from lupus patients showed increased levels of DKK1, suggesting altered canonical Wnt signaling in the development of lupus (56).…”
Section: Wnt/β-catenin Signaling In Dcs: a Potential Therapeutic Targmentioning
confidence: 99%